PEDAGOGICAL FOUNDATIONS OF TEACHING THE EDUCATIONAL, MORAL, AND SPIRITUAL IMPORTANCE OF KURASH SPORTS TO STUDENT YOUTH - Rakhimberdiyev J. N. (Bright Mind Publishing, 2025)
This article discusses the educational, moral, and spiritual importance of kurash sports in the upbringing of student youth, highlighting it as a means of moral-ethical education. Information is provided about how kurash, both in the educational process and in sports competitions, serves as a source of national pride and honor, and plays a significant role in the comprehensive development of the individual.
Keywords: Kurash sport, kurash wrestler, kurash science, kurash spirituality, scientific innovations in kurash, physical preparedness of kurash wrestlers, national values in kurash, kurash techniques, kurash philosophy.